(untitled) (International Conference on Computers in Education, 2022)
In this paper, the results of a cross-sectional study comparing two surveys on educational technology use are presented. The first survey included 1103 teachers and was completed in 2015 to explore the areas of in-class technology use, digital contents use, professional development, and other relevant issues in primary and secondary education in Croatia at the time. The second survey was administered seven years later and included 838 teachers in total. The two survey results were compared to identify changes in teachers’ educational technology use and related issues. The results show large increase in technology and digital contents use in everyday primary and secondary school classrooms confirming these tools become more widespread and more accepted nowadays. On the other hand, the analysis shows pedagogical, and teacher professional development issues remain challenges even after 7 years, indicating those areas should be the focus on attention in terms of educational technology sustained use.